2016
DOI: 10.1002/jssc.201501291
|View full text |Cite
|
Sign up to set email alerts
|

Efficient fabrication of high‐capacity immobilized metal ion affinity chromatographic media: The role of the dextran‐grafting process and its manipulation

Abstract: A novel high-capacity Ni 2+ immobilized metal ion affinity chromatographic medium was prepared through dextran-grafting process. The dextran-grafting degree of the media had a great effect on His-tagged protein binding performance. The maximum binding capacity was obtained as a certain thickness of dextran was grafted. 1041 Indirect enantioseparation of fluoxetine in mouse serum by derivatization with 1R-(-)-menthyl chloroformate followed by ultra high performance liquid chromatography and quadrupole time-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…One gram of suction‐dried Sepharose 4FF ® was mixed with 0.2 mL of ECH in sodium hydroxide solution by agitation at 50°C overnight. Then, the activated microspheres were washed with distilled water and then 1 mL of aqueous Dextran T40 solution (0.6 g/mL) was added in sodium hydroxide solution . Dextran‐grafted microspheres were washed with distilled water and activated with ECH in sodium hydroxide solution at 30°C for 6 h .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One gram of suction‐dried Sepharose 4FF ® was mixed with 0.2 mL of ECH in sodium hydroxide solution by agitation at 50°C overnight. Then, the activated microspheres were washed with distilled water and then 1 mL of aqueous Dextran T40 solution (0.6 g/mL) was added in sodium hydroxide solution . Dextran‐grafted microspheres were washed with distilled water and activated with ECH in sodium hydroxide solution at 30°C for 6 h .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies about dextran‐grafted chromatographic media focused on ion‐exchangers, studies were seldom reported dextran‐grafting process on affinity chromatographic media. In our group, novel dextran‐grafted metal chelating chromatographic medium was elaborately fabricated with binding capacity improved significantly . Whether the dextran‐grafting process is effective in enhancing the binding performance of affinity chromatographic media, and also, how the dextran‐grafting process improves the binding ability and the stability of the media are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal laser scanning microscopy evaluation CLSM has been popularly used for studying protein distribution when immobilized or bound to a chromatographic medium [31]. It provides the possibility of measuring the fluorescent emission of fluorescence dye within 3D objects with high local resolution and depth discrimination [32]. In this work, CLSM was used to visualize both nanodiscs coupling and CYP450 binding behavior in chromatographic medium (Figure 6).…”
Section: 6mentioning
confidence: 99%
“…Recently, polymer‐grafted chromatographic resins have been developed to improve the protein adsorption capacity and adsorption rates . These polymer‐grafted resins possess many polymer chains in the pores, which could provide 3‐D flexible binding for target protein and result in higher DBC than nongrafted resins . Dextran‐grafted resins are typical and could be prepared by the “grafting to” technique, i.e.…”
Section: Introductionmentioning
confidence: 99%